Sinus graft infection management: systematic review - Schlund, Matthias (2022)
The aim of this study was to systematically review sinus graft infection management in order to define which protocols should be implemented. The terms searched in each database were “sinus graft infection management”, “maxillary sinus lift infection”, “maxillary sinus graft infection”, “maxillary sinus elevation infection”, “maxillary sinus augmentation infection”. The outcome evaluated both maxillary sinus health and implantological result. The initial search yielded 1190 results. 18 articles were included counting 3319 patients and 217 sinus graft infections. In every study, all patients obtained finally a disease-free sinus but the outcome regarding the graft and the dental implant was more varied. It is not possible to define the best treatment protocol for sinus graft infections based on the published data since the level of evidence is poor. Management is very heterogeneous. This review highlighted the necessity of surgical treatment associated with antibiotic therapy.